Rule Based Reasoning for Student Learning Styles Identification - Sugiarto, Adi Putra; Kurniawan, Rio (Prosiding International conference on Information Technology and Business (ICITB), 2017)
Learning styles could determine the effectiveness of the learning process as the dominant trend or type of student learning styles in tune with the type and character of his brain. Differences in learning styles in the classroom can lead to gaps in the classroom because of the differences in  absorption of information based on the learning styles of each student. Based on the gaps in the classroom, we need a system that can grouping students to maximize the absorption of information when learning takes place. The process of grouping students will be divided into two stages: the application of a rule-based reasoning methods and  the use of the type of grouping.Tthe process of rule-based reasoning has 12 rules with variable auditory, visual and kinesthetic. Percentage of each variable and  the tendency of learning styles and  their advice  of students learning methods, from will be grouping in partitional clustering and the non-exclusive clustering. Questionnaire is done by  twenty users, first  user fill  the questionnaire with the percentage of 15% Auditory, 20% Visual and  65%  Kinesthetic so that the first  user has concluded Kinesthetic learning style. Clustering can maximize the absorption of information because the learning methods are applied  in accordance with learning styles of  students in a class. Keywords: Questionnaire, Rules, and Knowledge Base